Analisis Sikap Konsumen Pada Produk Kopi (Studi Kasus Pada Perusahaan Pdp Kahyangan Kabupaten Jember ) - Naning Retnowati; Alwan Abdurahman (Politeknik Negeri Jember, 2017)
The purposes of this research are to determine : 1) attributes criteria that are considered by consumer in coffee buying process, 2) consumer attitudes toward coffee product attributes of PDP Kahyangan than its competitor (Kapal Api Special). The method of data analysis used in this research is the Fishbein Attitude Model. This research uses eight attributes of product, those are colour, aroma, flavour, acidity, viscosity, package, price, product availability, and product recognition. Based on this research flavour, aroma and accidity attribute are the most considered by consumer in coffee buying decision process and then followed by viscosity, product availability, colour, product recognition, package, and price. The total value of consumer attitudes toward both PDP Kahyangan and Kapal Api Special are positive, that is with the value of 138,53, itâ€™s fewer than Kapal Api Special (162,85). Consumer attitude in flavour product attribute of PDP Kahyangan is better than Kapal Api Special, with the best value of 23,03. It showed that consumer acceptance flavour product attribute of PDP Kahyangan is is better than Kapal Api Special.Â